From Dialogue to Living Together: The Discussions on Inter-Religious Dialogue in Turkey since the Late 1990s - Furat, Ayşe Zişan (Interdisciplinary journal for religion and transformation in contemporary society, 2020)
Abstract Interreligious dialogue ( IRD ) has been one of the vehemently debated topics in Turkey since the late 90s. Many socio-political factors played a significant role in the proliferation of IRD discussions within the academic circles in this period. The multifaceted and complex nature of the term also attracted a wide audience outside the academia, and particularly, politically motivated organisations. Correspondingly, the term became one of the reference points for their propaganda goals. Facing the complexity of the issue, this paper aims to disclose the evolution of IRD in Turkey by seeking answers to the question “how has the term IRD been perceived by Turkish scholars?” by providing insights about the major milestones in the discussions. The article concludes with an analysis of the main trends in the related discussions as follows: IRD as (1) a necessity for social welfare, (2) an instrument for religious propaganda, (3) and as part of dialogic relation.